2001
DOI: 10.1006/jcis.2000.7227
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) Sorption Complexes on Montmorillonite as a Function of Solution Chemistry

Abstract: We have investigated the effect of changes in solution chemistry on the nature of uranyl sorption complexes on montmorillonite (SAz-1) at different surface coverages (1.43-53.6 µmol/g). Uranyl uptake onto SAz-1 between pH 3 and 7 was determined in both titration and batch-mode experiments. These pH values result in solutions that contain a range of monomeric and oligomeric aqueous uranyl species. Continuous-wave and time-resolved emission spectroscopies were used to investigate the nature of U(VI) sorbed to SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 45 publications
5
112
2
3
Order By: Relevance
“…Differences in U(VI) adsorption extent to quartz and ferrihydrite as compared to the results of Fox et al (2006) were noted that result from solid-liquid ratio effects. Direct comparisons are not easily made with other previous studies of U(VI) adsorption to smectites Morris et al, 1994;McKinley et al, 1995;Turner et al, 1996;Sylwester et al, 2000;Chisholm-Brause et al, 2001;Hennig et al, 2002;Chisholm-Brause et al, 2004;Kowal-Fouchard et al, 2004;Catalano and Brown, 2005) and quartz or amorphous silica (Glinka et al, 1997;Arnold et al, 1998;Gabriel et al, 2001;Froideval et al, 2003) because of differences in solution pH, U(VI) concentration, solid-to-liquid ratio, and carbonate concentration as well as the procedure of mineral preparation. U(VI) affinity varied by more than two orders of magnitude for the phyllosilicates with the highest K d values observed for chlorites, particularly the ones rich in Mg but poor in Fe (Table 3).…”
Section: U(vi) Adsorption Affinity On Reference Mineralsmentioning
confidence: 90%
“…Differences in U(VI) adsorption extent to quartz and ferrihydrite as compared to the results of Fox et al (2006) were noted that result from solid-liquid ratio effects. Direct comparisons are not easily made with other previous studies of U(VI) adsorption to smectites Morris et al, 1994;McKinley et al, 1995;Turner et al, 1996;Sylwester et al, 2000;Chisholm-Brause et al, 2001;Hennig et al, 2002;Chisholm-Brause et al, 2004;Kowal-Fouchard et al, 2004;Catalano and Brown, 2005) and quartz or amorphous silica (Glinka et al, 1997;Arnold et al, 1998;Gabriel et al, 2001;Froideval et al, 2003) because of differences in solution pH, U(VI) concentration, solid-to-liquid ratio, and carbonate concentration as well as the procedure of mineral preparation. U(VI) affinity varied by more than two orders of magnitude for the phyllosilicates with the highest K d values observed for chlorites, particularly the ones rich in Mg but poor in Fe (Table 3).…”
Section: U(vi) Adsorption Affinity On Reference Mineralsmentioning
confidence: 90%
“…Surface-complexation models accurately describe experimental adsorption results for U(VI) onto single-mineral phases (Waite et al 1994;Pabalan et al 1998;Arnold et al 2001;Chisholm-Brause et al 2001;Villalobos et al 2001;Hsi and Langmuir 1985;Dzombak and Morel 1990;Wazne et al 2003). In contrast, the application of SCM to soils and sediments has been challenging because of the poor understanding of the thermodynamics of surface-complex formation in natural systems (Barnett et al 2002;Davis et al 2004a;Kohler et al 1996).…”
Section: The Surface-complexation Model (Scm)mentioning
confidence: 99%
“…These surface complexes include mononuclear bidentate U(VI) hydroxyl complexes on hydrous ferric oxide (Manceau et al, 1992); inner-sphere edge complexes and outer-sphere basal plane complexes on smectite Source: (1) (Hsi and Langmuir 1985); (2) (Waite et al 1994); (3) (Mckinley et al 1995) ; (4) (Bargar et al 1999); (22) (Bargar et al 2000); (23) (Elzinga et al 2004); (24) (Sylwester et al 2000); ND indicates "not determined." (Chisholm-Brause et al 1994;Sylwester et al 2000;Chisholm-Brause et al 2001), and inner-sphere bidentate complexes, with the formation of polynuclear surface complexes at near-neutral pH on silica and alumina (Sylwester et al 2000). Time-resolved laser-fluorescence spectroscopy (TRLFS) revealed that a uranyl-tricarbonate complex formed on calcite at low surface loading (Elzinga et al 2004).…”
Section: Identification Of U(vi) Surface Complexing Speciesmentioning
confidence: 99%
“…[13][14][15] Adsorbents such as natural zeolite are cost-effective for the removal of uranium, although their modified versions tend to perform better. [13][14] It should be noted that at times this modification is not deliberate, but may be a result of natural processes in environments where the adsorbents are deployed. For instance, ammonium is one of the dominant components in aqueous systems and may influence the surface properties of such adsorbents.…”
Section: Introductionmentioning
confidence: 99%